Kajian potensi dan pengembangan ekowisata hutan mangrove di bandar Bakau Puteri Tujuh, Kota Dumai, Provinsi Riau - Fakhrurrozi Fakhrurrozi; Yusni Ikhwan Siregar; Zulkarnaini Zulkarnaini (Pelantar Press, 2018)
Mangrove forest area, Bandar Bakau Puteri Tujuh in Dumai City has been developed into the ecotourism forests. Empirical experience as well as issues about Bandar Bakau Puteri Tujuh such as: tourist motivation mangrove ecotourism activity, environmental pollution and is deemed necessary taken a study to the development of potentials. The main purpose of this research is: (1) to analize factor that attract tourist to conduct mangrove ecotourism activity in mangrove forest Bandar Bakau Puteri Tujuh area (2) calculate carrying capacity mangrove forests area (3) to provide sustainable mangrove forestsecotourism in Puteri Tujuh area. Survey on qualitative and descriptive approachwere done this study.Data were collected in the questionnaire and deep interview method. The research was carried out in August-Oktober 2015. It appeared that: factor attracting tourists to visit included the hospitality with result 91% tourists argues. Characteristics of the are were of suitable for education ecotourism activity and scenery enjoy ecotourism activity. It is suggestedto create sustainable mangrove ecotourism in Bandar BakauPuteriTujuh (1) Which need to developing more ecotourism activity for tourist. 2) Goverment with area organizer must be add to availability and repair facilities ecotourism mangrove activity (3) Need to Dumai City goverment regulations allotment status area and space arrangement plan Bandar BakauPuteriTujuh sphere as ecotourism mangrove area. 4) Hand over construct and specifically training for organizer about ecotourism development in cohesiveness